Mobile games about the Great Patriotic War in native (Tatar) language lessons - Akhtarieva R. F., Nurieva R. R. (University as a factor of Modernization of Russia: History and Prospects (to the 55th anniversary of the I.N. Ulyanov ChSU), 2024)
the article deals with the possibilities of using mobile games at the lessons of native (Tatar) language and their adaptation to the study of the history of our region, especially to the study of the heroes of the Great Patriotic War of the city of Yelabuga.
Keywords: история; Великая Отечественная война; культура; родной язык; history; Great Patriotic War; игры; culture; татарский язык; native language; мобильные игры; герои Великой Отечественной войны; mobile games; Tatar language; heroes of the Great Patriotic War; games